(1108) The System of Indicators of Economic Efficiency of Social Production used in Socialist Planning (Abstract) نظام مؤشرات الكفاءة الاقتصادية للإنتاج الاجتماعي المستخدم في التخطيط الاشتراكي (الملخص) - G. Galakhov. (INP., 2018)
Evaluation of economic efficiency of planned decisions adopted is the fundamental problem of planning at the present stage of development. it provides opportunities of determining correlation between expenditures and results achieved and choosing the most rational ways of national economy development.